2006
DOI: 10.1021/jm051231p
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Oral Drug Absorption Based on Absorption Rate Constants in Humans

Abstract: Models for predicting oral drug absorption kinetics were developed by correlating absorption rate constants in humans (K(a)) with computational molecular descriptors. The K(a) values of a set of 22 passively absorbed drugs were derived from human plasma time-concentration profiles using a deconvolution approach. The K(a) values correlated well with experimental values of fraction of dose absorbed in humans (FA), better than the values of human jejunal permeability (P(eff)) which have previously been used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 47 publications
4
55
0
1
Order By: Relevance
“…The best model reported by these researchers consisted of logD 5.5 , PSA and HBD. Another study by Linnankoski et al also revealed that HBD (and not HBA) was among the most important parameters describing the oral absorption rate constant (39). The reason for the importance of HBD in permeability might be the predominant presence of hydrogen bond acceptors in the head group regions of membrane bilayer lipids (11).…”
Section: Development Of a Predictive Model For Buccal Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The best model reported by these researchers consisted of logD 5.5 , PSA and HBD. Another study by Linnankoski et al also revealed that HBD (and not HBA) was among the most important parameters describing the oral absorption rate constant (39). The reason for the importance of HBD in permeability might be the predominant presence of hydrogen bond acceptors in the head group regions of membrane bilayer lipids (11).…”
Section: Development Of a Predictive Model For Buccal Permeabilitymentioning
confidence: 99%
“…However, in addition to these descriptors, HBD and nRotB were also found to be important in predicting buccal permeability. Previous studies have demonstrated that a greater hydrogen bonding capability, especially, the number of hydrogen bond donors, of a molecule decreases its permeability probably due to increased interactions with the lipid bilayer (14,39). In an earlier study by Winiwarter et al, the human jejunal permeability values of 13 passively absorbed compounds were correlated with several physicochemical descriptors using partial least squares (PLS) (40).…”
Section: Development Of a Predictive Model For Buccal Permeabilitymentioning
confidence: 99%
“…This is probably due to the different water solubility of pure matrine and crude matrine. Linnankoski et al (2006) have shown that drug absorption is determined mainly by the dissolution rate in the gastrointestinal fluids. Because pure matrine dissolves in water readily, it is rapidly absorbed by the rat.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Previously, it has been reported that the absorption of drug-like compounds in the human intestine can be predicted as accurately with computational models as with in vitro experiments (7). Even though quantitative structure-property relationship (QSPR) models for transdermal and intestinal absorption of drugs have been constructed (8)(9)(10), QSPR models for the corneal permeability are still at an elementary level. Some computational models for predicting the corneal permeability have been developed (2,(11)(12)(13)(14), but so many of these models have been constructed for a small set of similar compounds (2,13), and the models are thus not applicable to a broader variety of molecules.…”
Section: Introductionmentioning
confidence: 99%